Embrioscopía en aborto retenido Embrioscopy in missed abortion - Jesús Alberto Ruíz-Ruíz; Eugenia Corredor-Sánchez; Carlos Julio García-Perlaza; José Ignacio Madero-Cervera; Claudia Rocío López; María Fernanda León; Magally Escobar (Federación Colombiana de Obstetricia y Ginecología, 2006)
Objetivo: describir los hallazgos por embrioscopía transcervical en pacientes con aborto retenido, de diferentes semanas de gestación en primer trimestre. Institución: Medifértil, Bogotá, Colombia. Materiales y métodos: estudio descriptivo tipo serie de casos. Pacientes con aborto retenido diagnosticado por ecografía; se describe el cariotipo de la muestra obtenida por legrado obstétrico posterior al procedimiento de embrioscopía. Resultados: el procedimiento fue realizado exitosamente a las seis pacientes, cuatro de las cuales presentaron alteraciones fenotípicas todas con cariotipo normal, un caso presentó trisomía 21 sin alteraciones fenotípicas y un caso en que se identiﬁcó degeneración hidrópica, correspondió a una mola parcial. Conclusión: la embrioscopía transcervical previa al legrado obstétrico podría ser una alternativa diagnóstica útil, principalmente en pacientes con pérdida temprana posterior a reproducción asistida y pérdida recurrente de la gestación. Objective: showing the early experience and the ﬁndings in six patients suffering missed miscarriage having different weeks of gestation, who received transcervical embrioscopy before obstetric curettage whilst receiving the same anesthesia. Institution: Medifértil, Bogotá, Colombia. Type of Study: descriptive series of cases. Materials and methods: kariotyping and trans-cervical embrioscopy was carried out on each of the six patients having a previous diagnosis of missed miscarriage, conﬁrmed by transvaginal ultrasonography during the ﬁrst three months. Results: transcervical embrioscopy was successfully done on all the patients; four of them (66%) exhibited phenotype abnormalities, every case displayed a normal kariotype (analysis of 30 methaphases). One of the cases expressed a trisomy 21 and the other corresponded to hydropic degeneration related to partial mole. Conclusion: We suggest applying transcervical embrioscopy before obstetric curettage in patients diagnosed as having early and recurrent loss as a complementary tool for identifying genetic abnormalities. It is also a procedure having low morbidity and uses the same hysteroscopy infrastructure.